Znak miejski Zduńskiej Woli - Adamczewski, Marek (Biuletyn Szadkowski, 2014)
The heraldic coat of arms of Zduńska Wola commemorates the possessors of the town (Stefan and Honorata Złotniccy) and the granting of city rights in 1825. The present sign of the city of Zduńska Wola was designed in 1915. Earlier, in 1847 and 1904, two proposals for coats of arms were prepared, which, however, were not accepted as city emblems. In 19th century, adoption of a coat of arms depicting three bees was considered, and in early 20th century a city sign was created featuring a factory, a loom and a woman working on it. The 1847 version was popularized in the period of ll Republic and then in the 1960s by Marian Gumowski. Up to 1976 it competed for the status of the city sign with the emblem designed in 1915. Resolution of the City Council of Zduńska Wola of 1976 put a stop to this dispute, although it comes up from time to time to this day.